2022
DOI: 10.21608/ejhm.2022.249227
|View full text |Cite
|
Sign up to set email alerts
|

CT Characterization of COVID-19 Infection: Analysis of 1000 PCR Positive Cases in First and Second Waves

Abstract: Background: There is a wide variety of CT radiological findings of COVID-19 infection, this study aimed to analyze retrospectively the similarities and differences of CT radiological findings between first and second waves in the confirmed coronavirus patients. Materials and methods: comparative retrospective study between two COVID-19 pandemic waves was conducted on 1000 patients who were diagnosed as COVID-19 patients, at Assiut University hospital, 500 patients in the period from May 2020 to August 2020, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…Te study found that GGO and consolidations were the most common chest CT features among COVID-19 patients during both waves. Furthermore, bilateral lung involvement with lower lobe involvement was predominantly seen in both waves which were in comparative agreement with previous knowledge [9,19,20]. Traction bronchiectasis and mediastinal lymphadenopathy, delayed CT features of COVID-19, were seen predominantly among the frst-wave patients [9].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Te study found that GGO and consolidations were the most common chest CT features among COVID-19 patients during both waves. Furthermore, bilateral lung involvement with lower lobe involvement was predominantly seen in both waves which were in comparative agreement with previous knowledge [9,19,20]. Traction bronchiectasis and mediastinal lymphadenopathy, delayed CT features of COVID-19, were seen predominantly among the frst-wave patients [9].…”
Section: Discussionsupporting
confidence: 91%
“…Novel coronavirus disease 2019 (COVID- 19) is a viral infectious disease that was frst detected in Wuhan, Hubei Province of China in 2019 [1]. It is a multisystem syndrome with a spectrum of presentation ranging from asymptomatic disease to life-threatening complications requiring invasive management like extracorporeal membrane oxygenation [2].…”
Section: Introductionmentioning
confidence: 99%